In Search of Serenity: Religious Struggle Among Patients Hospitalized for Suspected Acute Coronary Syndrome - Magyar-Russell, Gina (Journal of religion and health, 2014)
Hospitalization for a sudden cardiac event is a frightening experience, one that is often marked by uncertainty about health status, fear of recurrent cardiac problems, and related existential, religious, and spiritual concerns. Religious struggle, reflecting tension and strain regarding religious and spiritual issues, may arise in response to symptoms of acute coronary syndrome (ACS). The present study examined the prevalence and types of religious struggle using the Brief RCOPE, as well as associations between religious struggle, psychological distress, and self-reported sleep habits among 62 patients hospitalized with suspected ACS. Fifty-eight percent of the sample reported some degree of religious struggle. Questioning the power of God was the most frequently endorsed struggle. Those struggling religiously reported significantly more symptoms of anxiety, depression, and sleep disturbance. Non-White participants endorsed greater use of positive religious coping strategies and religious struggle. Results suggest that patients hospitalized for suspected ACS experiencing even low levels of religious struggle might benefit from referral to a hospital chaplain or appropriately trained mental health professional for more detailed religious and spiritual assessment. Practical means of efficiently screening for religious struggle during the often brief hospitalization period for suspected ACS are discussed.